ADVANCES IN ORTHOPEDIC SURGERY: MINIMALLY INVASIVE TECHNIQUES FOR THE TREATMENT OF COMPLEX LOWER LIMB FRACTURES - Antonia Rocha Fiorott, Maria; Siqueira Neto, José; Martins Eller, Lara; Brandão Coelho, Ingrid; Dadalto Scarpati, Elza; Sarlo Pinheiro, Alice; Altoé Pipa Silva, Ivelize; Maia Cruz Brazuna, Ricardo; Cesar Ferreira, Alex; Maria Moreno Lobo, Marcelle; Castro Narduci, Jessica; Vita de Sá, Julia; et al. (Health and Society, 2024)
Orthopaedic surgery has undergone significant evolution with the development of minimally invasive techniques (MIT) for the treatment of complex lower limb fractures. These innovations have transformed orthopaedic management, offering less traumatic and more effective alternatives to traditional procedures. IMTs are designed to reduce tissue damage, speed up recovery and minimize post-operative complications, making them increasingly relevant in today’s orthopaedic scenario. The aim of this study is to discuss recent advances in minimally invasive techniques in orthopaedic surgery for complex lower limb fractures. The research explores the benefits of these techniques, the challenges faced in clinical practice and the future prospects for their widespread adoption. The research was based on a literature review, with a qualitative approach, using the PubMed, Google Scholar, and Scielo databases. For a comprehensive and relevant analysis of the advances and challenges of minimally invasive techniques in orthopaedic surgery, specific descriptors reflecting the area of study were applied, with a time frame covering publications from 2018 to 2023. The analysis is based on a review of up-to-date literature, including clinical studies and meta-analyses that demonstrate the efficacy and safety of minimally invasive techniques. Innovations such as the use of external fixators, locked intramedullary rods and surgical navigation systems are highlighted. These approaches allow for precise stabilization of fractures with smaller incisions and less impairment of soft tissue vascularization. In addition, advances in intraoperative imaging and surgical instrumentation are discussed, which have improved the precision of procedures and reduced operative time. Challenges such as the learning curve and the cost of the technologies are also addressed. Thus, advances in minimally invasive techniques have revolutionized orthopaedic surgery, offering effective solutions for the treatment of complex lower limb fractures. Despite the challenges, such as the need for specialized training and investment in new technologies, the benefits for patients, including shorter recovery times and better functional results, are undeniable. The future of orthopaedic surgery will continue to benefit from these innovations, with the potential to further increase access and the quality of treatments.